Long-term survival in a patient with unresectable liver metastases from uveal melanoma treated with transarterial chemoembolization with irinotecan eluting beads – case report and review of literature - Stanisławska, Katarzyna; Stadnik, Honorata; Nawrocki, Mikołaj; Ramlau-Piątek, Katarzyna; Juszkat, Robert; Drews, Michał (Contemporary Oncology/Współczesna Onkologia, 2017)
Introduction : Treatment of unresectable liver metastases (LM) from uveal melanoma (UM) remains a major clinical challenge. Systemic chemotherapy and chemoimmunotherapy regimens extrapolated from cutaneous melanoma are considered to be ineffective in therapy of metastases from uveal melanoma. Studies suggest that the progression of hepatic metastases rather than the primary tumor or metastases in other organs determines survival. Case report : We report a case of transarterial chemoembolization of 57-year-old man diagnosed with unresectable liver metastases from uveal melanoma with irinotecan eluting beads. Therapy resulted in long progression free survival and overall survival, 41 months and 45 months after diagnosis of metastatic disease respectively. Patient did not experience any major side effects of the therapy. Follow-up CTs indicate stable disease in mRECIST criteria and partial response in CHOI criteria. Conclusions : Transarterial chemoembolization with drug eluting beads loaded with irinotecan may be an effective treatment of unresectable liver metastases from uveal melanoma.